Market Competition, Financialization, and Green Innovation: Evidence From China’s Manufacturing Industries - Guo, Yineng; Fan, Lijun; Yuan, Xiaohao (Frontiers in Environmental Science, 2022)
Green innovation has become a critical measure to address the sustainable development challenges of manufacturing industries, and research has largely neglected the important role of managers as decision-makers within firms. Using a sample of China’s listed manufacturing firms from 2009 to 2019, this study explores the impact of market competition and financialization on corporate green innovation and examines the moderating effect of market competition. The main findings are as follows. First, intense market competition may inhibit corporate green innovation in the context of the Chinese market. Second, managers are willing to sacrifice firms’ long-term interests in exchange for profits in the short run. Third, market competition alleviates the negative association between financialization and corporate green innovation, indicating that the interactions between manufacturing firms may alter managers’ preferences for financial investment. In addition, our study explores heterogeneous impacts of market competition and financialization on corporate green innovation, and the empirical results are consistent with our findings in most cases. Our findings provide support for rational resource allocation in green innovation and can be used to guide manufacturing firms to achieve their goals of sustainable development.